Proceedings of the Ocean Drilling Program 1992
DOI: 10.2973/odp.proc.sr.129.117.1992
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic through Early Cretaceous Sedimentation History of the Central Equatorial Pacific and of Sites 800 and 801

Abstract: Sedimentation in the central Pacific during the Jurassic and Early Cretaceous was dominated by abundant biogenic silica. A synthesis of the stratigraphy, lithology, petrology, and geochemistry of the radiolarites in Sites 801 and 800 documents the sedimentation processes and trends in the equatorial central Pacific from the Middle Jurassic through the Early Cretaceous. Paleolatitude and paleodepth reconstructions enable comparisons with previous DSDP sites and identification of the general patterns of sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 127 publications
1
28
0
Order By: Relevance
“…A nominal mass accumulation rate (MAR) of 1.5 g cm −2 kyr −1 (15 t km −2 yr −1 ) for the Tethyan equatorial belt 5 • S-5 • N was derived from estimates for the Cretaceous equatorial Pacific Ocean (Ogg et al, 1992), which is within the range of values found for the Cenozoic equatorial Pacific (Mitchell and Lyle, 2005;Mitchell et al, 2003).…”
Section: Climmentioning
confidence: 96%
“…A nominal mass accumulation rate (MAR) of 1.5 g cm −2 kyr −1 (15 t km −2 yr −1 ) for the Tethyan equatorial belt 5 • S-5 • N was derived from estimates for the Cretaceous equatorial Pacific Ocean (Ogg et al, 1992), which is within the range of values found for the Cenozoic equatorial Pacific (Mitchell and Lyle, 2005;Mitchell et al, 2003).…”
Section: Climmentioning
confidence: 96%
“…Sites with rocks spanning the J/K boundary have been targeted by the International Ocean Discovery Program (IODP) (and earlier incarnations). This program has included sites in (i) the Indian Ocean (Brown, 1992;Gradstein et al, 1992;Kaminski, Gradstein & Geroch, 1992), with evidence for a cooler water regime; (ii) the Pacific Ocean, which is thought to have had a stable circulatory regime (Matsuoka, 1992;Ogg, Karl & Behl, 1992); and (iii) the Atlantic Ocean with a distinct North-South salinity gradient (Deroo, Herbin & Roucaché, 1983;Kotova, 1983;Gradstein et al, 1992). In the Late Jurassic, western Tethys and Atlantic ecosystems were fuelled by a high-nutrient flux, leading to high levels of phytoplankton and radiolarites, possibly driven by shifting circulatory regimes as continental configurations changed (Baumgartner, 1987;Weissert & Mohr, 1996;Danelian & Johnson, 2001).…”
Section: Environmental Changes During the Late Jurassic-early Crementioning
confidence: 99%
“…; 400 k.y.) of Milankovitch climate-oceanographic cooling cycles (e.g., Molinie andOgg, 1992a, 1992b;Ogg et al, 1992). This eccentricity modulation of precession should also cause overall cooling-warming cycles of the deep ocean, thereby creating rises and falls of eustatic sea level (e.g., Revelle, 1990).…”
mentioning
confidence: 99%